Acute environmental hypoxia potentiates satellite cell‐dependent myogenesis in response to resistance exercise through the inflammation pathway in human. Issue 1 (10th December 2019) - Britto, Florian A.; Gnimassou, Olouyoumi; De Groote, Estelle; Balan, Estelle; Warnier, Geoffrey; Everard, Amandine; Cani, Patrice D.; Deldicque, Louise
Abstract: Acute environmental hypoxia may potentiate muscle hypertrophy in response to resistance training but the mechanisms are still unknown. To this end, twenty subjects performed a 1‐leg knee extension session (8 sets of 8 repetitions at 80% 1 repetition maximum, 2‐min rest between sets) in normoxic or normobaric hypoxic conditions (FiO2 14%). Muscle biopsies were taken 15 min and 4 hours after exercise in the vastus lateralis of the exercised and the non‐exercised legs. Blood samples were taken immediately, 2h and 4h after exercise. In vivo, hypoxic exercise fostered acute inflammation mediated by the TNFα/NF‐κB/IL‐6/STAT3 (+333%, +194%, + 163% and +50% respectively) pathway, which has been shown to contribute to satellite cells myogenesis. Inflammation activation was followed by skeletal muscle invasion by CD68 (+63%) and CD197 (+152%) positive immune cells, both known to regulate muscle regeneration. The role of hypoxia‐induced activation of inflammation in myogenesis was confirmed in vitro. Acute hypoxia promoted myogenesis through increased Myf5 (+300%), MyoD (+88%), myogenin (+1816%) and MRF4 (+489%) mRNA levels in primary myotubes and this response was blunted by siRNA targeting STAT3. In conclusion, our results suggest that hypoxia could improve muscle hypertrophic response following resistance exercise through IL‐6/STAT3‐dependent myogenesis and immune cells‐dependent muscle regeneration.